Machinery risk assessment during warehouse racking installation / Fatimah Nadhirah Isa - Fatimah Nadhirah, Isa (2017)
In any work site, hazard and risk are the most common criteria that are needed to be reduce, minimize, or eliminate to assure a safety workplace for employees. Machinery and power tools were commonly used in a racking installation. Forklift, reach truck, and scissor lift contributed in the building of the warehouse racking installation. However, the machinery were also contributed to high risk for the workers. Hazard and risk of machinery needed to be analyze before start of any work. One of the method that was used for hazard identification and risk assessment was Hazard Identification, Risk assessment, and Rick Control (HIRARC) method. This research study analyze the risk developed by machinery during warehouse racking installation located in Telok Panglima Garang site. The identification of hazard was done through inspection and observation on site. Every job task on site were analyzed and evaluated by following the HIRARC method. Questionnaire survey method was done on 30 workers with a purpose in determined the safety awareness during work and handling machinery. By using the HIRARC method, 25 job hazards have been identified as medium level hazard, and 2 job hazard have been identified as high level risk hazard. Physical hazard have been identified as the highest numbered type of hazard on site. Control measures were given based on the result obtained from the survey and the risk rating.